Intro to Android application development (video sneak peek) - Galpin, Dan.; Safari eBooks ([S.l.] : Addison-Wesley Professional : mylivelessons.com, 2010)
"Mobile application developer Dan Galpin takes you through a streamlined, fast-paced introduction into developing applications for the latest Android platform. Developers will learn how to create a series of simple, functional, Android applications that take advantage of features unique to the Android platform. It details aspects of handling application resources, creating Android user interfaces, networking, and important concepts such as application lifecycle, interoperation, and multithreading. The target audience for the video is developers familiar with the Java programming language, but who may not have previous experience with mobile development. This is a Sneak Peek preview version of the Intro to Android Application Development Video. "--Resource description page.
System requirements: Adobe Flash Player, version 8 or higher; or QuickTime Player, version 7.2 or higher; or Windows Media Player, version 11 or higher.
Description from resource description page (viewed June 16, 2010).
Keywords: Android (Electronic resource); Application software -- Development; Open source software; Mobile computing; Electronic books